Spatial and temporal abundance and distribution of Stomolophus meleagris (Rhizostomae: Stomolophidae) in a lagoon system southern Gulf of Mexico - Félix, Francisco Javier (2017)
The scyphomedusae feed mainly on microscopic crustaceans, eggs and fish larvae, molluscs and some other jellyfishes. The distribution and abundance of the scyphomedusae has an economic and ecological impact as they are predators that have an influence on the population dynamics of other fisheries. This investigation took place in the lagoon system ‘Arrastradero-Redonda’, Tabasco, from September 2013 to August 2014, with the purpose to provide information on the distribution, and spatial and temporal abundance of Stomolophus meleagris; along with its relation to environmental parameters. A total of 10 stations were defined and biological samples were taken on a monthly basis during this annual cycle. For this purpose, three pulls with a beach seine monofilament (20m long by 3m height, mesh opening 1.5 cm, 5 to 10 minutes) per station were made within a 1 km2 area. Information obtained was used to calculate the fishing efficiency analysis (CPUE con org./Evaluated Area Unit) and to determine the relationship with the environmental parameters. Our results showed that the abundance in the stations 1 to 3 was from 7 to 19 org./km2 from April to August 2014; less organisms were observed in stations 6 to 10 (an average of 1 org./km2) from October 2013 to March 2014. The multiple correlation steps analysis indicated that there is a strong association between the CPUE and some environmental investigated variables, and a 70.9 % variability of the data was observed. The salinity resulted the most important variable because it determined a 64.3 % of variation; it was followed by the temperature with a 3.6 %; meanwhile, dissolved oxygen explained only the 2.9 %, this was mainly because within the area there are several geological, oceanographic and biological factors that favor the distribution of this species due to seawater contribution through the Tupilco bar. With the provided data with this investigation we were able to determine the fishery potential of this resource for Tabasco state. However, additional research is required to allow an extended quantification of this resource, to determine the commercial exploitation areas, and drive studies about reproductive and feeding habits, that may provide the necessary information to establish plans for sustainable use.